CYTOTOXIC, α-CHYMOTRYPSIN AND UREASE INHIBITION ACTIVITIES OF THE PLANT Heliotropium dasycarpum L. - Ghfaffari, Muhammad Abuzar; Chaudhary, Bashir Ahmed; Uzair, Muhammad; Ashfaq, Khuram (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The aim of this study was to investigate Cytotoxic, α-Chymotrypsin and Urease inhibition activities of the plant Heliotropium dasycarpum. Materials & Methods: Dichloromethane and methanol extracts of the plant were evaluated for cytotoxic, α-Chymotrypsin and Urease inhibition by using in vivo Brine Shrimp lethality bioassay and in vitro enzymatic inhibition assays respectively. Results: The methanol extract of the plant exhibited significant cytotoxic activity. Out of 30 brine shrimp larvae, 2 (6%), 26 (86%) and 28 (93%) larvae were survived at concentration of 1000μg/ml, 100μg/ml and 10μg/ml respectively with LD50; 215.837. Similarly 21 (70%), 25 (83%), 29 (96%) larvae were survived of dichloromethane plant extract with LD50; 6170.64. The methanol and dichloromethane extract exhibited 10.50±0.18% and 41.51±0.15% α-chymotrypsin enzyme inhibition respectively with IC50 values of greater than 500 μmol. The methanol extract showed 24.39±0.21% Urease enzyme inhibition with IC50 values of greater than 400 μmol. While dichloromethane extract has 11.46±0.09% enzyme inhibition with IC50 values of greater than 500 μmol. Conclusion: The results clearly indicated that Heliotropium dasycarpum has cytotoxic potential and enzyme inhibition properties. Further study is needed to screen out antitumor and anti-ulcerative agents.